2002
DOI: 10.1016/s0092-8674(01)00632-8
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of the Rotavirus mRNA 3′ Consensus by an Asymmetric NSP3 Homodimer

Abstract: Rotaviruses, the cause of life-threatening diarrhea in humans and cattle, utilize a functional homolog of poly(A) binding protein (PABP) known as nonstructural protein 3 (NSP3) for translation of viral mRNAs. NSP3 binds to viral mRNA 3' consensus sequences and circularizes the mRNA via interactions with eIF4G. The X-ray structure of the NSP3 RNA binding domain bound to a rotaviral mRNA 3' end has been determined. NSP3 is a novel, heart-shaped homodimer with a medial RNA binding cleft. The homodimer is asymmetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
67
0
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(75 citation statements)
references
References 39 publications
5
67
0
3
Order By: Relevance
“…To our knowledge, there is no precedent of such an asymmetric homodimer with distinct subunit structures, except for the N-terminal domain homodimer of nonstructural protein 3 (NSP3) from rotavirus (41). NSP3 binds to the viral mRNA and circularizes it for translation.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there is no precedent of such an asymmetric homodimer with distinct subunit structures, except for the N-terminal domain homodimer of nonstructural protein 3 (NSP3) from rotavirus (41). NSP3 binds to the viral mRNA and circularizes it for translation.…”
Section: Discussionmentioning
confidence: 99%
“…A colon shows a conserved amino acid between GBR and GAR, or GBR and GCR. The RNA-binding domain (Deo et al, 2002) is indicated by a line above the sequences. Shaded regions indicate a-helices (H1-H8) and b-strands (S1-S3) in the RNA-binding domain.…”
Section: Discussionmentioning
confidence: 99%
“…Among the NSP3 sequences of GBRs, the N-terminal 120 aa region was highly conserved and corresponded to the RNA-binding region revealed for GAR NSP3 (Deo et al, 2002) (Fig. 4).…”
Section: Full-genome Analysis Of Human Group B Rotavirusmentioning
confidence: 99%
“…The region of NSP3 that is necessary for its interaction with RoXaN I includes a portion of the NSP3 dimerization domain and is close to the eIF4G-binding domain (44). Dimerization of NSP3 is required for its eIF4G-and RNAbinding properties (13,22,44), and consequently, for its biological properties (61). By interacting with NSP3, RoXaN I could impair the binding of eIF4G to NSP3, either by disrupting NSP3 dimers or by concealing its eIF4G-binding site.…”
Section: Vol 78 2004mentioning
confidence: 99%
“…The amino-terminal domain (aa 1 to 150) is required for sequencespecific RNA binding (13,44). Our laboratory has shown that a dimer of NSP3 binds a single RNA molecule (44), and the three-dimensional structure of the amino terminus of NSP3 confirms this, showing a heart-shaped dimer bound to one RNA molecule (13). The central domain of NSP3 (aa 150 to 241) is predicted to form a coiled-coil structure, allowing NSP3 dimerization (44).…”
mentioning
confidence: 99%